Topical Issues of Investment Property Accounting (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Investment real estate (MI) plays an important role in diversifying risks and ensuring profitability. However, in the countries of Eastern Europe and Central Asia, approaches to accounting for MI often do not comply with international standards, which makes it difficult to accurately reflect its value in financial statements. The paper analyzes the problems of accounting for MI, models (initial cost and fair value), valuation methods and ways to increase the transparency of reporting solutions, including the introduction of unified accounts and the adaptation of international standards, which improves accounting and increases the investment attractiveness of companies.